An Approach to Nonsymmetric Bis(tertiary phosphine oxides) Comprising Heterocyclic Fragments via the Pd-Catalyzed Phosphorylation - Zakirova, Gladis G.; Mladentsev, Dmitrii Yu.; Borisova, Nataliya N. (Synlett, 2020)
Nonsymmetric tertiary phosphine oxides with different five- and six-membered heterocyclic fragments such as pyridine, 2,2′-bipyridine, 1,10-phenantroline, quinoline, imidazole, and thiazole were synthesized in good yields via the successive introduction of phosphine oxide groups into the initial dihalogenated heterocycles by means of Pd-catalyzed phosphorylation reaction. The synthesis of pyridine-type compounds is hindered by competing double coupling, while for five-membered heterocycles the principal difficulty is the dehalogenation. Both side processes were successfully suppressed by the use of an excess of a dihalide (which can be easily recovered during the product purification step), proper phosphine ligand for palladium, and nonpolar solvent such as toluene.
Keywords: cross-coupling; phosphorylation; nonsymmetric phosphine oxide; palladium; heterocycles; dehalogenation